2018
DOI: 10.1017/s0007114518002611
|View full text |Cite
|
Sign up to set email alerts
|

Maternal protein intake during pregnancy is associated with child growth up to 5 years of age, but not through insulin-like growth factor-1: findings from the ROLO study

Abstract: Infant protein intake has been associated with child growth, however, research on maternal protein intake during pregnancy is limited. Insulin-like growth factors (IGF) play a role in early fetal development and maternal protein intake may influence child body composition via IGF-1. The aim of this study was to investigate the association of maternal protein intake throughout pregnancy on cord blood IGF-1 and child body composition from birth to 5 years of age. Analysis was carried out on 570 mother–child dyad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
1
16
0
2
Order By: Relevance
“…We found that the increased body weight tended to diminish toward adulthood. This finding might be explained by the adaptation response, i.e., slower growth rate in the growing stage/fattening period of pigs [21]. Furthermore, we found that the IGF-1R protein content was increased, which was associated with elevated serum T3 levels at birth due to HP exposure.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…We found that the increased body weight tended to diminish toward adulthood. This finding might be explained by the adaptation response, i.e., slower growth rate in the growing stage/fattening period of pigs [21]. Furthermore, we found that the IGF-1R protein content was increased, which was associated with elevated serum T3 levels at birth due to HP exposure.…”
Section: Discussionmentioning
confidence: 57%
“…It has been reported that hypothyroidism is closely linked to body weight and the growth rate of offspring in early life [ 37 39 ]. Indeed, a recent study revealed that maternal high-protein diet consumption during pregnancy causes elevated body weight of offspring at birth without changing the IGF-I pathway [ 21 ]. Similarly, we demonstrated that T3 and T4 levels in the serum were higher in the HP-exposed piglets with higher body weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of protein intake during pregnancy on FGR and LBW delivery have not been fully elucidated. Namely, meeting the minimum protein requirement may be helpful to prevent the risk of FGR [ 31 , 32 , 33 , 34 , 35 ], while a higher protein intake may do more harm than good [ 32 , 35 , 36 ]. It has been proposed that there is a quadratic (inverse U-curve) relationship between maternal protein intake and fetal growth [ 35 , 37 ], and moderate protein intake with an appropriate energy/protein balance is required to optimize fetal growth [ 35 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal nutrition during pregnancy can affect maternal health during pregnancy and beyond . It also influences the intrauterine environment of the developing fetus and this may influence the health and development of children in utero right through to adulthood . Therefore, nutrition during pregnancy is an important consideration in the management of pregnant women and in the overall life course approach to health care and health promotion.…”
Section: Introductionmentioning
confidence: 99%